Obscured quasars at high redshift in the UKIDSS Ultra Deep Survey. Issue Volume 9:Issue S304(2013) (25th July 2014) - Botti, Ismael; Almaini, Omar; Hartley, Will; Mortlock, Alice; Lira, Paulina
Abstract: Obscured quasars hidden in deep X-ray surveys can be recovered by looking at mid-infrared wavelengths, where dust re-radiates the absorbed radiation. Here we present a sample of obscured quasars in the redshift range 1 < z < 4 based on data from the UKIDSS Ultra-Deep Survey (UDS), the deepest near-IR survey over ~ 1 sq. deg. to date. Candidates that are primarily selected by their 24 μm emission are probed by decomposing their spectral energy distribution (SED) to disentangle the emission from the AGN and its host galaxy. We show preliminary results on their host galaxy properties as well as their clustering, showing that obscured quasars are found in galaxies located in the green valley, residing in dark matter haloes not different from normal galaxies at those redshifts.